Molecular Characterization of Biofilm-related Virulence and Resistance genes in Candida albicans Isolates from Women with Vulvovaginitis - Ahmadessa, Solhan Mustafa; Ali, Solaf Jawhar (Kurdistan Journal of Applied Research, 2025)
One of the most prevalent reasons for gynecologic consultations is vulvovaginitis (VV), particularly vulvovaginal candidiasis (VVC). The etiology of VVC mostly associated with Candida albicans (C. albicans). The recurrence of VVs and the development of resistance to antimicrobials, along with efforts to find therapeutic alternatives are of paramount importance. Thus, this study aims to find the prevalence C. albicans virulence, resistance genes in addition to its susceptibility to antifungals. In this case control study, a total of 125 high vaginal cotton swabs attained in duplicate. from 100 wome clinically diagnosed with VVC and 25 controls (non-VVC). C. albicans was isolated with Hicrome differential agar and confirmed with species-specific primers using Polymerase chain reaction. Genes of the studied virulence determinants, Aglutinin-Like-Sequence (ALS1, ALS3), Hyphal Wall Protein1 (HWP1) as well as resistance determinants associated such as multidrug-resistance (MDR1) and Candida drug resistance (CDR1, CDR2) were also tested. The prevalence of Candida species were 70% and 32% in case and control groups, respectively. Further, the frequency of C. albicans were 88.57% (case group) and 100% (control group). The most common virulence gene was ALS3, present in 96.7% of case group and 87.5% of control group. Additionally, the results indicated that 98.39% of case group and 100% of control group exhibited MDR1 and CDR2 from confirmed isolates of C. albicans. Lastly, the result showed the highest antifungal resistance rates in case group were against voriconazole (70.97%) and fluconazole (40.32%), whereas in control the antifungal resistance was 75% for both voriconazole and fluconazole. In conclusion, high rate of virulence and resistance genes amongst women with VVC and therefore, the study suggests the importance of these genes to be targeted in new antifungal drugs.